(untitled) (TAMADDUN NURI JURNALI, 2024)
This article discusses the basis of the appearance of the image of Alqama in Huvaido‘s work, the artistic and ideological analysis of the story about Alqama in the epic “Rohati Dil” and the importance of the art of quotation in Huvaido‘s work. The author’s unique style of image creation is analyzed.